Development and Validation of Academic Writing Textbook Based on Process Genre Approach for University Students - Helaluddin Helaluddin; Mohammed H. Al Aqad; Hengki Wijaya; Jusmianti Anwar; Nyayu Lulu Nadya; Syafryadin Syafryadin (STAI Hubbulwathan Duri, 2021)
The textbook is a practical learning tool for improving student writing skills; however, not all students learn from a textbook. For this reason, a lecturer must be able to design a textbook according to the needs of students. This paper describes developing and validating academic writing textbooks with a process genre approach in tertiary institutions. This research is part of the research development process, which consists of three phases: need assessment, design, and validation. Five experts were appointed to validate this academic writing textbook. Content Validity Index (CVI) is used to calculate the validity of textbooks quantitatively, with a score above 0.79 considered to meet the criteria. The validity test results state that the CVI of an academic writing textbook is 0.9, with a few revisions based on expert input and suggestions. These findings indicate that this textbook has good validity and reliability and can be used to write in college.